2019
DOI: 10.1002/ceat.201900012
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Performance of Al‐Decorated and Al/Mg Co‐Decorated Spray‐Dried CaO‐Based CO2 Sorbents

Abstract: The sharp loss-in-capacity in CO 2 capture as a result of sintering is a major drawback for CaO-based sorbents used in the calcium looping process. The decoration of inert supports effectively stabilizes the cyclic CO 2 capture performance of CaO-based sorbents via sintering mitigation. A range of Al-decorated and Al/Mg co-decorated CaO-based sorbents were synthesized via an easily scaled-up spraydrying route. The decoration of Al-based and Al/Mg-based supports efficiently enhanced the cyclic CO 2 capture capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…For instance, TiO 2 and Al 2 O 3 were simultaneously used by Peng et al 186 187 In this case, Y 2 O 3 was selected to induce an enhancement of the cyclic stability, whereas MgO was selected to improve the CO 2 uptake capacity (by means of an increased porous space for the carbonation reaction to take place). A spray drying approach was, similarly, proposed by Sun et al 188 to produce Al 2 O 3 /MgO-stabilized CaO-based sorbents, obtaining good results in terms of both enhanced multicyclic CO 2 sorption performances and CO 2 uptake (which was found to be larger than that typical of Al 2 O 3 -stabilized CaO-based sorbents).…”
Section: Multicyclic Decline Of Cao Reactivity and Technological Solu...mentioning
confidence: 99%
“…For instance, TiO 2 and Al 2 O 3 were simultaneously used by Peng et al 186 187 In this case, Y 2 O 3 was selected to induce an enhancement of the cyclic stability, whereas MgO was selected to improve the CO 2 uptake capacity (by means of an increased porous space for the carbonation reaction to take place). A spray drying approach was, similarly, proposed by Sun et al 188 to produce Al 2 O 3 /MgO-stabilized CaO-based sorbents, obtaining good results in terms of both enhanced multicyclic CO 2 sorption performances and CO 2 uptake (which was found to be larger than that typical of Al 2 O 3 -stabilized CaO-based sorbents).…”
Section: Multicyclic Decline Of Cao Reactivity and Technological Solu...mentioning
confidence: 99%
“…This concept is carried out by dispersion of CaO on an inert matrix (Ca x Al y O x +1.5 y , MgAl 2 O 4 , MgO, CaTiO 3 , etc. ), which is similar to supported catalysts by depositing active components on a catalyst support. Hu et al screened 12 inert supports for CaO by using the same wet-mixing method. Among them, Y-based and Al-based CaO showed the best CO 2 cyclic performance .…”
Section: Chemical Looping Regenerationmentioning
confidence: 99%
“…Results showed that the CaO/Ca 9 Al 6 O 18 sorbent capacity decreased from 0.275 g of CO 2 /g of sorbent at the first cycle to 0.197 g of CO 2 /g of sorbent at the 21st cycle. Despite decent performance in a lab-scale test, the water removing step in sol–gel methods is time-consuming and energy-intensive, which could be issues at large scale. , …”
Section: Chemical Looping Regenerationmentioning
confidence: 99%
“…When the mass ratios of Y 2 O 3 and MgO were 20 wt %, respectively, the synthetic sorbent achieved notably high CaO conversion (over 90%) at harsh conditions (carbonation, 650 °C, 15 vol % CO 2 , and 15 min; calcination, 900 °C, N 2 , and 8 min) and was stabilized at a CO 2 uptake of 0.311 g CO 2 /g sorbent even after 122 cycles. Similarly, Sun et al synthesized a range of Al 2 O 3 -supported and Al 2 O 3 /MgO co-supported CaO-based sorbents, respectively, using an easily scalable spray drying approach . They also found that the addition of Al 2 O 3 or Al 2 O 3 /MgO both effectively enhanced the cyclic CO 2 capture performance of the CaO-based sorbents, while the cumulative CO 2 uptake of Al 2 O 3 /MgO co-supported CaO-based sorbents was generally higher than that of Al 2 O 3 -supported sorbents.…”
Section: Synthetic Cao-based Sorbentsmentioning
confidence: 99%